48th AIAA/ASME/SAE/ASEE Joint Propulsion Conference &Amp;amp; Exhibit 2012
DOI: 10.2514/6.2012-3993
|View full text |Cite
|
Sign up to set email alerts
|

Aircraft System Study of Boundary Layer Ingesting Propulsion

Abstract: A trade-factor-based system study has been carried out to identify fuel burn benefits associated with boundary layer ingestion (BLI) for generation-after-next (N+2) aircraft and propulsion system concepts. The analysis includes detailed propulsion system engine cycle modeling for a next-generation, Ultra-High-Bypass (UHB) propulsion system with BLI using the Numerical Propulsion System Simulation (NPSS) computational model. Cycle modeling was supplemented with one-dimensional theory to identify limiting theore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
74
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(75 citation statements)
references
References 4 publications
(9 reference statements)
1
74
0
Order By: Relevance
“…However, the benefit was lower: the analysis of the BWB developed for the Cambrigde-MIT Silent Aircraft Initiative (SAX40) resulted in a PSC of up to four percent. A similar value is reported in [5] for a BWB derived from the SAX40 aircraft. On the experimental side, the investigations with the model of the D8 aircraft (double bubble) have to be mentioned .…”
Section: Boundary Layer Ingestionsupporting
confidence: 63%
See 1 more Smart Citation
“…However, the benefit was lower: the analysis of the BWB developed for the Cambrigde-MIT Silent Aircraft Initiative (SAX40) resulted in a PSC of up to four percent. A similar value is reported in [5] for a BWB derived from the SAX40 aircraft. On the experimental side, the investigations with the model of the D8 aircraft (double bubble) have to be mentioned .…”
Section: Boundary Layer Ingestionsupporting
confidence: 63%
“…Since it is a mature technology, new concepts such as boundary layer ingestion (BLI), which is closely connected to embedded engines, have to be taken into account to get a relevant benefit. Previous studies in this field revealed a promising potential for all kinds of aircraft concepts [3][4][5][6][7] and encouraged the present work. The intention was to develop a fast tool for basic performance analyses of a single propulsor in the presence of BLI and it should be decoupled from a concrete aircraft design.…”
Section: Introductionmentioning
confidence: 88%
“…Hardin, et al 15 used an NPSS model of a typical ultra-high bypass (UHB) turbofan engine to determine performance changes due to BLI-type distortion. To account for performance losses due to reduced fan efficiency and increased inlet total pressure losses, the engine's TSFC sensitivity to various values of fan efficiency and inlet total pressure recovery was calculated in NPSS.…”
Section: Bli Studiesmentioning
confidence: 99%
“…As mentioned in [4,5,7]; BLI requires a deeper and broader analysis in aspects such as PAI, engines installation, flow control, inlet design, and mainly, it is required to analyse the effect of BLI in the performance of the whole aircraft, not only in the propulsion system. This work examines, at a preliminary design stage, another potential benefit of BLI.…”
Section: Introductionmentioning
confidence: 99%
“…These studies determined aerodynamic coefficients for both configurations and evaluated the Propulsor-Airframe Integration (PAI) through computational fluid dynamics (CFD) and wind tunnel experiments at high Reynolds numbers about 75 million and a Mach number of 0.85 [6]. Whilst, Hardin [7] estimated the fraction of viscous drag that could be ingested, and determined that BLI propulsors can reduce from 3% up to 5% the fuel burn rate, for BLI fractions between 10% and 12% (Drag ingested/ Total Drag). All the aforementioned works were conducted on baseline configurations of BWB transport aircrafts.…”
Section: Introductionmentioning
confidence: 99%